Experiment on CO2–based combined cooling and power cycle: A multi-mode operating investigation. (1st May 2022) - Zhang, Yonghao; Shi, Lingfeng; Tian, Hua; Li, Ligeng; Wang, Xuan; Sun, Xiaocun; Shu, Gequn
Graphical abstract: Highlights: An experimental prototype of CO2 -based combined cooling and power cycle is developed. Multi-mode operations are achieved to accommodate diversified energy desires and heat source conditions. Dynamic characteristics during mode-switching are comprehensively investigated. The power and refrigeration output will be improved when respectively switching the combined cooling and power mode to power-alone mode and cooling-alone mode. Abstract: Combined cooling and power cycle is a high-profile way to improve energy utilization efficiency and mitigate energy issue. As a clean and environmentally friendly working fluid, CO2 has received growing attention in both power and refrigeration fields for its excellent properties and flexible application forms. Hence, CO2 -based combined cooling and power cycle becomes a natural choice especially in scenarios with diversified energy desires. Despite many current theoretical explorations devoted to CO2 -based combined cycle, experimental investigation is essential and obbligato to validate its flexibility in practical application. In this work, an experimental prototype of CO2 -based combined cooling and power cycle is developed to fill the gaps in experimental aspect. The prototype system can realize three operating modes, namely power-alone mode, simultaneous cooling and power mode and cooling-alone mode, so as to accommodate diversified energy desires and heat source conditions. The dynamic characteristics of mode-switching process as well as the systematic performance between different modes are particularly investigated. The results reveal that a longer settling time is required for switching cooling-alone mode to simultaneous cooling and power mode, which is approximately 380 s. While the response speed is much faster when switching from power-alone mode to simultaneous cooling and power mode, with an average settling time of 159 s. Remarkably, switching the combined cycle from simultaneous cooling and power mode to power-alone mode or cooling-alone mode will either improve the power output or refrigeration output, concurrently ameliorating the effectiveness of heat transfer in the coupling condenser. The ultimate outputs of the combined cycle in the three modes are 5.8 kW power at power-alone mode, 3.2 kW power and 8.0 kW refrigeration at simultaneous cooling and power mode as well as 9.8 kW refrigeration at cooling-alone mode in the present tests.